태극권 운동이 류마티스관절염 환자의 주관적 증상, 체력, 우울 및 자기효능감에 미치는 효과: 3개년 자료를 바탕으로 - 손정태; 황혜영; Son, Jung Tae; Hwang, Hye-Young (근관절건강학회지, 2018)
Purpose: The purpose of this study was to evaluate whether subjective symptoms, physical fitness, and emotional variables were improved after participating in a 6-week Tai Chi program in patients with rheumatoid arthritis. Methods: 23 rheumatoid arthritis patients participated in the Yang style Tai Chi for arthritis patients 90 minutes session conducted twice a week at the Arthritis Center of D University Hospital. The main outcome of current studies included self-reported scores of subjective symptoms(pain, sleep satisfaction, and fatigue), physical fitness tests, and depression (PHQ-9) and self-efficacy investigated with questionnaire before and after participating in Tai Chi. Results: After participating in Tai Chi, participants perceived lesser pain (t=2.61, p=.016) and fatigue (Z=-2.32, p=.020), and reported improved sleep satisfaction (t=-3.56, p=.002). In the physical fitness test, there were significant improvement in muscle strength (upper limb: t=-7.19, p<.001, lower limb: t=-4.86, p<.001), and balance (right t=-3.70, p=.001; left t=-2.30, p=.031). Depression (t=3.87, p=.001) and self-efficacy (Z=-3.44, p=.001) improved significantly after participating in Tai Chi. Conclusion: Tai Chi had beneficial effects on subjective symptoms and emotional variables as well as physical fitness. Therefore, the program could be recommended in the patients with rheumatoid arthritis.